Kierunki zmian w prawie o bezpieczeństwie morskim - Nawrot, Justyna (Studia Prawa Publicznego, 2019)
The article tackles the issue of amendments to Polish maritime safety law which has been amended a number of times since it came to life several years ago. The last amendments of 2015 have been the most profound and complex. Today, maritime safety is given much more importance than several dozen years ago. The public and private aspects of maritime safety became the focus of attention rather recently but are now a branch of law that is developing the most dynamically. As has been shown in the paper, although private maritime law was already known in the Ancient Times, public-private law regulations were adopted only after the sinking of the Titanic in 1912. Still, it is not the private but the public aspects of maritime safety law which constitutes the major challenge. The abundance of international and European legislation ought to prompt the Polish legislator to consider a possible adoption of one comprehensive maritime safety act which would approach the whole matter in question in a systematic manner. The deliberations presented in the paper sum up the amendments to maritime safety law made so far. They are also an attempt to analyse the new legal order more deeply, and propose some more general de lege ferenda conclusions. The analysis is set in a wider context, taking into account the amendments introduced to international and EU regulations.